Agridoc International - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Bureau pour le developpement de la production agricoleA documentary support service for developing countries has been set up in France by the Ministry of Cooperation and is run by the Office for the Development of Agricultural Production (BDPA)....